PWE-209 Orai inhibition prevents cytosolic ca2+ overload and acute pancreatitis. (22nd June 2015) - Wen, L; Voronina, S; Javed, MA; Awais, M; Szatmary, P; Latawiec, D; Chvanov, M; Collier, D; Barrett, J; Begg, M; Stauderman, K; Dunn, M; et al.
Abstract : Introduction: Cytosolic calcium overload triggers pancreatic acinar injury induced by pancreatitis toxins. Sustained Ca 2+ elevation depends on Ca 2+ entry through store-operated Ca 2+ entry (SOCE) channel Orai1, but the role of which in experimental acute pancreatitis (EAP) and human pancreatic acinar cell injury has not been determined. Method: Confocal and patch clamp technology were used to examine the effects of GSK-7975A and CM_128, inhibitors of SOCE channel Orai1 on bile acid-, hystimulation-, thapsigargin-, or cyclopiazonic acid-induced calcium entry into murine and human pancreatic acinar as well as human Orai1/STIM1-transfected HEK 293 cells. The effects of GSK-7975A and CM_128 on human necrotic pancreatic acinar cell death pathway activation induced by bile acid were monitored. EAP was induced by seven hourly intraperitoneal cerulein injections (50 mg/kg), retrograde pancreatic ductal TLCS infusion (50 mL 3 mM) or two hourly intraperitoneal injections of 150 mg/kg palmitoleic acid and 1.35g/kg ethanol. Different doses of either compound were tested in three diverse clinical representative models of EAP, begun at different time point after disease induction. EAP severity was assessed by standard biochemical parameters and blinded histopathology. Results: GSK-7975A and CM_128 inhibited toxin-induced SOCE and/or Ca 2+ release-activated Ca 2+ currents in a concentration-dependent manner up to >90% of control in all cells tested and significantly inhibited murine and human necrotic pancreatic acinar cell death pathway activation (p < 0.05). Administration of GSK-7975A or CM_128 after induction of EAP had pronounced inhibitory effects on all local and systemic disease parameters in all three models (all p < 0.05), demonstrating both dose- and time-dependency, with significantly greater effectiveness in a range of parameters when given one hour rather than six hours after disease induction. Conclusion: This study confirms the pivotal role of cytosolic calcium overload in the pathogenesis of acute pancreatitis and provides robust preclinical validation for Orai inhibition as a treatment for acute pancreatitis. Disclosure of interest: L. Wen: None Declared, S. Voronina: None Declared, M. Javed: None Declared, M. Awais: None Declared, P. Szatmary: None Declared, D. Latawiec: None Declared, M. Chvanov: None Declared, D. Collier: None Declared, J. Barrett Employee of: GlaxoSmithKline, M. Begg Employee of: GlaxoSmithKline, K. Stauderman Employee of: CalciMedica, M. Dunn Employee of: CalciMedica, A. Tepikin: None Declared, D. Criddle: None Declared, R. Sutton: None Declared.